Nonplanar Helicene Benzo[4]Helicenium for the Precise Treatment of Renal cell Carcinoma. Issue 11 (15th September 2021) - He, Xiaozhen; Gan, Fuwei; Zhou, Yan; Zhang, Yuanliang; Zhao, Peipei; Zhao, Bingru; Tang, Qianyun; Ye, Li; Bu, Jun; Mei, Junyang; Du, Ling; Dai, Huili; et al.
Abstract: Immune and targeted therapy are becoming the first‐line treatment for renal cell carcinoma (RCC). However, therapeutic outcomes are limited due to the low efficiency and side effect. Here, it is found that helicenes are able to exhibit an anticancer capability through changing the molecular structure from planar to nonplanar. Furthermore, the cytotoxicity in vitro and cancer inhibition ability of nonplanar helicenes increase with its aromatic rings' number. It is further demonstrated that benzo[4]helicenium shows the specific killing efficiency against the RCC cancer as compared to normal kidney cells. This is majorly originated from a more selective damage of benzo[4]helicenium for mitochondria and DNA in RCC cancer cells, not the normal kidney. The selective killing ability of benzo[4]helicenium makes it have potential to be used as a targeted drug for the precise treatment of RCC. Abstract : Benzo[4]helicenium effectively kills the renal cell carcinoma, which is majorly from a more damage for mitochondria and DNA through selectively inhibiting the DNA replication and repair in RCC cells.